2001
DOI: 10.1023/a:1010293325482
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two Cytoplasmic Male Sterile lines were crossed with fourteen restorer lines of rice widely grown in the western regions of Maharashtra, India, to produce 28 F1 hybrids which were evaluated for eight agronomically important traits, contributing to yield potential, in replicated field trials. The hybrid performance was recorded along with heterosis and heterobeltiosis. All the rice lines under investigation were subjected to marker-based variability analysis. An attempt was made to correlate genetic distance ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Thus authors reiterated that significant difference between the above studies may be used for prediction of heterosis in the silkworm breeding programme similar to the reports of plant breeding programmes [12,16,17] . The optimum level of genetic distance is necessary to obtain heterosis.…”
Section: Resultsmentioning
confidence: 65%
“…Thus authors reiterated that significant difference between the above studies may be used for prediction of heterosis in the silkworm breeding programme similar to the reports of plant breeding programmes [12,16,17] . The optimum level of genetic distance is necessary to obtain heterosis.…”
Section: Resultsmentioning
confidence: 65%
“…plus the best linear unbiased prediction (BLUP), some scientists identified marker loci associated with quantitative trait loci for hybrid performance or specific combining ability (SCA) in maize and rice [4][8], [16]. These studies showed the high potential of joint analyses of hybrids and parental inbred lines for the prediction of performance of untested hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigated the relation between DNA-marker variation of parents and heterosis as expressed by their hybrid. For example, in maize, genetic distance between parents was strongly correlated to heterosis of their hybrid (20). It should be noted, however, that other studies reported low or no correlation at all between marker distance and yield, and it is well accepted that this association depends, at least in part, on the type of crop and the germ plasm being used.…”
Section: Resultsmentioning
confidence: 98%